Does early regional scientific leadership translate into lasting innovation advantage? - Dragan Filimonovic; Christian Rutzer; Jeffrey T. Macher; Rolf Weder (University of Basel, Center of Business and Economics (WWZ), 2024)
We examine whether 'pioneer' regions - early leaders in generating new ideas in emerging scientific fields - develop and maintain an innovation advantage in the same fields over time. Our analysis covers 24 disruptive technologies (e.g. AI, cloud computing) in thousands of OECD regions over 20 years. The results show that pioneer regions gain a significant and growing innovation advantage over non-pioneer regions. This advantage is most pronounced in "super-cluster" regions, which are leaders in both science and related innovation. These findings highlight the importance of early scientific leadership for sustained regional innovation and suggest important policy implications.
Keywords: O30; O33; R11; 330; Science; Innovation; Regional Advantage; Emerging Technology